The Role of the Financing Structure indicators in The growth of Bank` Ownership Rights (Applied study in Syrian Islamic banks) (Damascus University Journal for the economic and Political sciences, 2025)
The financing decision attracts the attention of financial departments in banks because its effects and results are linked to the decisions taken, and banks are considered highly sensitive to their sources of funds due to the specificity of their dealings with money as deposits and investments. Therefore, they should harmonize between the internal sources of their funds and the external sources of them represented by deposits in a way that allows them to reduce costs and increase profits.Therefore, the study aimed to demonstrate the role of some indicators of the financing structure in the growth of property rights of Syrian Islamic banks, and to achieve the objectives of the study, the descriptive approach was relied upon in the study of previous literature related to the financing structure of Islamic banks. It also adopted the analytical approach by testing hypotheses and analyzing data derived from annual reports. For all Islamic banks listed on the Damascus securities Exchange during the time period (2011-2021) based on the Eviews12 statistical program.The study concluded that there is a direct relationship between the ratio of equity to assets with the growth rate of equity, while the relationship was inverse with the rate of return on equity. The ratio of deposits to assets was also associated with a positive direct relationship with the rate of return on equity and the growth rate of equity.
Keywords: Financing Structure; Ownership Rights; Syrian Islamic Banks; Damascus Securities Exchange